The legacy of Serbian architectural exports to countries in Africa: hotel architecture (1960–1999) - Antešević, Nebojša; Gubić, Ilija (Arhitektura i urbanizam, 2025)
In the corpus of Serbian architectural exports to African countries from the 1960s to the end of the 1990s, the completed and conceptual/competitive solutions for hotel architecture, the subject of this article, stand out. After liberation from colonial administrations in the 1950s and 1960s, there was enthusiasm and optimism in the independent African countries for the formation of modern societies, accompanied by the extensive construction of state administration buildings, various social institutions and housing. Design and construction companies from S.F.R. Yugoslavia played a significant role in this, with their construction experience in the decades after World War II and capacity to meet the various needs and requirements of clients. At the same time, new hotels were built, which were important firstly in the context of social change and the establishment of international cooperation, and then for the development of the tourist industry in African countries. From the 1970s, after the construction of facilities with primary state and social functions, the development of tourism also began to intensify, bringing new investments, transport infrastructure and improved service activities to developing African countries. The resorts, hotels, safari hotels and other forms of catering and tourist architecture that emerged in the 1980s as a result of the desire to develop mass tourism in certain African countries brought new opportunities to contemporary architecture on the African continent. Tourism also played an important role in the promotion of authentic cultural and geographical features, so that the architecture of hospitality and tourist facilities proved to be a good way of marketing certain concepts and spatial and design solutions that convey the impression of local specificities to foreign guests. Although most of the tourist architecture projects by Serbian authors were not implemented, their architectural concepts, design features and freer approaches, often inspired by the influences of postmodernism, point to more progressive trends in contemporary architecture in African countries.
Keywords: architects from Serbia; African countries; hotel architecture; architectural export; modernism; regionalism; tropical architecture